Introduction to Python programming in finance - Tang, Jiayun (Nanyang Technological University, 2020)
The project aims to explore effective and efficient education terminologies in teaching beginners to master Python programming. As beginners who want to study Python programming may come from different educational backgrounds, such as finance major or computer science major, different teaching styles should be customized for them in order to achieve the best outcome. To help students master Python programming and apply to their respective domain, this report proposes a concept of ‘block-based project’ to help beginners to start with Python programming with greater ease and interest. Moreover, two block-based projects, one for finance students and another for computer science students, have been designed and presented. Lastly, an integrated Python programming education platform, Let’s Python, has been established to enhance students’ study experience.